2002
DOI: 10.1128/aac.46.8.2525-2532.2002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of Entecavir against Lamivudine-Resistant Hepatitis B Virus Replication and Recombinant Polymerases In Vitro

Abstract: Entecavir (ETV) is a potent and selective inhibitor of hepatitis B virus (HBV) replication in vitro and in vivo that is currently in clinical trials for the treatment of chronic HBV infections. A major limitation of the current HBV antiviral therapy, lamivudine (3TC), is the emergence of drug-resistant HBV in a majority of treated patients due to specific mutations in the nucleotide binding site of HBV DNA polymerase (HBV Pol). To determine the effects of 3TC resistance mutations on inhibition by ETV triphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(129 citation statements)
references
References 35 publications
10
117
2
Order By: Relevance
“…Rather, the appearance of the M184V mutation likely reflects the fact that it abolishes the anti-HIV activity of entecavir ( Figures 2C and 2D). Interestingly, selection of the M184V mutation in HIV RT could be anticipated since structural models show that the M184V corresponds to the HBV pol mutation, rtM204V (23), which decreases HBV susceptibility to entecavir (24). In both cases, the targeted methionine is in the YMDD motif at the active site.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, the appearance of the M184V mutation likely reflects the fact that it abolishes the anti-HIV activity of entecavir ( Figures 2C and 2D). Interestingly, selection of the M184V mutation in HIV RT could be anticipated since structural models show that the M184V corresponds to the HBV pol mutation, rtM204V (23), which decreases HBV susceptibility to entecavir (24). In both cases, the targeted methionine is in the YMDD motif at the active site.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was shown that lamivudine resistant mutants are not sensitive to L-pyrimidine analogs such as emtricitabine, clevudine, elvucitabine, telbivudine while they remain susceptible to purine analogs such as adefovir, tenofovir, and to some extent to entecavir (Delaney et al, 2001;Fu and Cheng, 2000;Levine et al, 2002;Menne et al, 2002;Seigneres et al, 2002). The adefovir resistant strains are also sensitive to lamivudine, emtricitabine, and entecavir, and to some extent to tenofovir (Angus et al, 2003;Villeneuve et al, 2003).…”
Section: Prevention Of and Combating Drug Resistancementioning
confidence: 99%
“…In vitro studies have shown that entecavir effectively suppresses the replication of lamivudine-resistant HBV with an EC 50 of 0.026 lM [22]. The selection of the 1 mg dose of entecavir for evaluation in the current study in lamivudine-refractory patients resulted from a multinational phase II dose-ranging study in which entecavir 1 mg demonstrated superior efficacy to continued lamivudine 100 mg, and yielded the greatest viral load reduction compared with the other doses of entecavir studied (0.5 and 0.1 mg) [23].…”
Section: Introductionmentioning
confidence: 99%